Bioenergetic Failure Drives Functional Exhaustion of Monocytes in Acute-on-Chronic Liver Failure - Maheshwari, Deepanshu; Kumar, Dhananjay; Jagdish, Rakesh Kumar; Nautiyal, Nidhi; Hidam, Ashinikumar; Kumari, Rekha; Sehgal, Rashi; Trehanpati, Nirupama; Baweja, Sukriti; Kumar, Guresh; Sinha, Swati; Bajpai, Meenu; et al. (Frontiers in Immunology, 2022)
Objective: Monocyte-macrophage system is central to host innate-immune defence and in resolving injury. It is reported to be dysfunctional in Acute-on-Chronic-Liver-Failure (ACLF). The disease-associated alterations in ACLF monocytes are not fully understood. We investigated the mechanism of monocytes functional exhaustion and the role of Umbilical Cord Mesenchymal stem cells (ucMSC) in re-energizing monocytes in ACLF. Design: Monocytes were isolated from peripheral blood of ACLF-patients (n=34) and matched healthy controls (n=7) and patients with compensated cirrhosis (n=7); phagocytic, oxidative burst and bioenergetics were analysed. In the ACLF mouse model, umbilical cord mesenchymal stem cells (ucMSCs) were infused intravenously, and animals were sacrificed at 24-hours and Day-11 to assess changes in monocyte function, liver injury and regeneration. Results: Patients with ACLF [alcohol 64%] compared to healthy controls and compensated cirrhosis had increased monocyte-macrophages in the liver and a number of peripheral blood monocytes (p<0.0001) which displayed significant defects in phagocytic (p<0.0001) and oxidative burst capacity (p<0.0001). ACLF patients also showed a significant increase in the number of liver macrophages as compared to healthy controls (p<0.001). Bioenergetic analysis showed markedly reduced oxidative phosphorylation (p<0.0001) and Glycolysis (p<0.001) in ACLF monocytes. Patients with monocytes having maximum mitochondrial respiration of <37.9pmol/min (AUC=0.822, Hazard ratio [HR]=4.5) and baseline glycolysis 42.7mpH/min (AUC=0.901, HR=9.1) showed increased 28 days mortality (p<0.001). Co-culturing ACLF monocytes with ucMSC showed improved mitochondrial respiration (p<0.01) and phagocytosis (p<0.0001). Further, ucMSCs therapy increased the monocyte energy (p<0.01) and phagocytosis (p<0.001), reduced hepatic injury and enhanced hepatocyte regeneration in ACLF animals. Conclusion: Bioenergetic failure drives functional exhaustion of monocytes in ACLF. ucMSCs resuscitate monocyte energy and prevent their exhaustion. Restoring monocyte function can ameliorate hepatic injury and promote liver regeneration in animal model of ACLF.